A Study on the Prosecutor’s Presupposition Strategies in Courtroom - Wang, Yaqi (Journal of Educational Research and Policies, 2024)
As technology improves by leaps and bounds, forensic linguistics, as a separate and interdisciplinary research field, has attracted the attention of a growing number of scholars. The purpose of courtroom discourse is clearer than that of everyday language. In a trial, all parties involved, whether judges, prosecutors, defense attorneys or defendants, are committed to achieving their stated goals through a variety of linguistic strategies and techniques. And presupposition itself is a highly purposeful linguistic strategy. As a result, judges, prosecutors and lawyers often use the technique of presupposition to obtain information in their own favor in court interrogations. From the perspective of forensic linguistics, this paper uses the theory of presuppositions, including semantic and pragmatic presuppositions, to provide a qualitative analysis of real cases in courtroom. The results show that the application of presuppositions in court allows the prosecutor to control the defendant's answers to a certain extent and has a positive effect in their own favour.